2004
DOI: 10.1093/jac/dkh436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carvacrol and eugenol as prophylaxis and treatment of vaginal candidiasis in an immunosuppressed rat model

Abstract: Carvacrol and eugenol could be considered as promising products in the treatment of vaginal candidiasis. This work is a preliminary contribution to the development of a new generation of efficient and natural antifungal agents for curative treatment and prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 30 publications
4
57
0
2
Order By: Relevance
“…Fungal inoculums were prepared from overnight culture found values between 0.28 and 1.27 mg mL -1 for bacteria and from 0.65 to 1.27 mg mL -1 for fungi, which are similar to the values found in our study (7,16).…”
Section: Inoculum Preparationsupporting
confidence: 89%
See 2 more Smart Citations
“…Fungal inoculums were prepared from overnight culture found values between 0.28 and 1.27 mg mL -1 for bacteria and from 0.65 to 1.27 mg mL -1 for fungi, which are similar to the values found in our study (7,16).…”
Section: Inoculum Preparationsupporting
confidence: 89%
“…Some studies suggest that oregano exerts a therapeutic effect when administered to rats experimentally infected with (4,10). The effects of oregano essential oil on yeasts of medical importance such as Candida albicans isolated from human patients have also been studied (7,11,16). However, data concerning the impact of essential oils on yeasts of the genus Candida isolated from the vaginal mucous membrane of female dogs and other animals with a diagnosis of candidiasis are scarce to date.…”
Section: Most Antifungals Currently Available For the Treatment Of DImentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that administrations of tea tree oil 9) and essential oil components, terpinen-4-ol, 10) carvacrol and eugenol, 11) decreased the viable number of C. albicans when the rat vaginal candidiasis model was used. Although these results seem to contradict ours, we think this difference may depend on experimental conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Mondello et al reported that intravaginal injection of tea tree oil 9) or its main active compound, terpinen-4-ol, 10) just 1 h after intravaginal inoculation of C. albicans reduced significantly, but not remarkably, viable cell number of C. albicans in vaginal cavity in rat models. Chami et al reported that carvacrol and eugenol 11) effectively reduced the cell number, however, these compounds are not suitable for clinical use because of their irritant activity.…”
mentioning
confidence: 99%